Comparison of the effects of Diplen LX membrane and Coe-Pak on pain, wound healing, and patient preference after the periodontal flap surgery in patients with moderate to severe chronic periodontitis - Mehrnoosh Sadighi; Masoumeh Faramarzi; Reza Pourabbas; Zeinab Torab; Hamidreza Mohammadi; Salar Hoseein Nazmi (Tabriz University of Medical Sciences, 2022)
Background. After periodontal surgery, in most cases, the surgical area is covered with a surgical pack. It has been suggested that these packs might minimize complications. This study aimed to compare the effects of Diplen LX membrane and Coe-Pak on pain, wound healing, and patient preference after a periodontal flap surgery in patients with moderate to severe chronic periodontitis. Methods. In this randomized clinical trial, 26 patients were evaluated. Pain scores were assessed using visual analog scale (VAS) on the 3rd and 7th days postoperatively and compared between the two dressings. On the 7th and 14th days after both flap surgeries, surgical site healing was evaluated using the wound healing index (WHI). Results. The mean age of the patients was 31. It was observed that the severity of pain in the studied patients on the 3rd and 7th days postoperatively was significantly lower in the intervention group than in the control group. It was also observed that the value of WHI in the studied patients on the 7th and 14th days postoperatively was significantly higher in the intervention group than in the control group. Conclusion. The pain was less severe in both groups using periodontal dressing and also lower in the Diplen LX membrane group. In addition, based on WHI, wound healing score in patients was also higher and more favorable in the Diplex LX membrane group. Due to the above factors, the majority of patients preferred the use of the Diplen LX membrane.